2022
DOI: 10.3389/fpsyt.2022.904283
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Online High-Intensity Interval Training (HIIT) on Psychological Symptoms in Students in Lockdown During the COVID-19 Pandemic: A Randomized Controlled Trial

Abstract: ObjectiveWe aimed to evaluate the feasibility of an online High-Intensity Interval Training (HIIT) program on clinical psychological symptoms in higher education students in the context of the COVID-19 pandemic lockdown.Materials and MethodsDuring the lockdown, 30 students aged 18–25 years, who had been screened previously with a cut-off score ≥5 in the Generalized Anxiety Disorder-7 (GAD-7) questionnaire, were randomly assigned to either the 4-week HIIT program with three sessions per week conducted through o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 48 publications
0
41
2
Order By: Relevance
“…Analysis of the results revealed that HIIT reduced both stress and depressive symptoms in the study group. The results suggest that this type of intervention has good tolerance (at a participation rate of 87%) and has the potential to counter mental problems among young people [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the results revealed that HIIT reduced both stress and depressive symptoms in the study group. The results suggest that this type of intervention has good tolerance (at a participation rate of 87%) and has the potential to counter mental problems among young people [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, four were supplemented by an additional follow-up examination [ 27 , 29 , 30 , 35 ]. An analysis of the statistical methods used revealed that three authors used univariate pre-post methods (Wilcoxon test, t-test, Mann-Whitney U test) [ 34 , 35 , 38 ], six authors used linear models [ 27 , 29 , 32 , 33 , 36 , 37 ], three studies employed analysis of variance [ 28 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 spreads worldwide, many studies have been published, all of which report the effects of physical exercise alone on muscles and quality of life after hospital discharge [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. However, published studies have generally reported muscle strength after rehabilitation exercises and have not looked specifically at the underlying mechanisms affecting muscle or other organs [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. For this purpose, a review study was conducted to investigate the importance of exerkines in COVID-19 patients discharged from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“… Body mass index of patients with COVID-19 discharged from the hospital [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation